Ghanaian SMEs’ perspective on the interrelationship between market and entrepreneurial orientations (REGE Revista de Gestão, 2022)
Purpose – This research examines the interrelationships between market orientation (MO) and entrepreneurial orientation (EO) in the small- and medium-sized enterprise (SME) sector. Due to the conflicting results associated with each orientation’s influence on firm performance, some researchers advanced that scholars should resort to concurrent observation of the constructs. To the researchers, concurrent deployment of the constructs by businesses is likely to result in an enhanced performance. However, what is lacking in their proposition is how the deployment of these resources should be, thereby leading to a knowledge gap in the literature. The aforementioned gap is what this paper seeks to address.Design/methodology/approach – The study employed deductive research approach, and data were collected from 366 SMEs’ owners or owner-managers of SMEs in two metropoles in Ghana. For this study, the hand delivery and collection of questionnaire technique was deployed. The reason is that most respondents may be reluctant to respond to the questionnaires through the post or Internet. Partial least square-structural equation modelling (PLS-SEM) was employed for the data analysis due to its importance in allowing the testing of relationships among constructs. Furthermore, seven-point Likert scale was used to generate responses from the respondents.Findings – The result indicates that MO and EO have a positive and significant influence on each other. However, the influence of EO on MO is greater. Therefore, when owners of SMEs are embracing the two constructs in their businesses, EO should precede MO. The finding is a novelty of this study. Through this result, the owners of SMEs would have knowledge of embracing EO before MO during the employment of the two constructs in their firms. The study further revealed that not all the components of MO have positive and significant influence on EO, and the reverse is true. Without this study, the owners of SMEs would have placed equal attention on each construct and their components. The study also indicates that deployment of MO in its composite form rather than components is the best way for improving EO.Practical implications – The more SMEs engage in MO activities, the likelihood of an increase in their entrepreneurial spirit and the opposite is true. However, engaging in more EO activities would result in higher MO than the reverse.Originality/value – The findings add to the empirical literature by revealing the interrelationships between MO and EO, which serve as a guide to owners of SMEs and practitioners in their concurrent deployment of the two constructs. The findings would also open replication doors for future researchers in different settings.